(untitled) - Zahradnikova, Zuzana (Aura musica, 2021)
The contribution reflects the new work of Slovak composers, whose compositions were based on a text of the Psalms. The mentioned compositions are the output of the KEGA project, which was solved in the last three years at the Department of Music, Catholic University in Ruzomberok and whose main goal was to enrich the repertoire of contemporary sacred music, both in the academic and artistic environment.
Keywords: psalms; sacred music; Slovak composer; compositions for choir; contemporary music